Análise e caracterização dos perfis dos empreendimentos e empreendedores do município de Doutor Severiano – RN - Gama, Antonio Carlos da Costa (Universidade Federal Rural do Semi-Árido, 2019)
In importance to the great growth of entrepreneurs in Brazil, the analysis and characterization of entrepreneurs in cities is essential. In this work a study was carried out in the commercial center of the city of Doutor Severiano, located in the state of Rio Grande do Norte. Thus, it becomes extremely important to collect data in order to obtain information that can be used to characterize entrepreneurs. The research instrument used for the development of the work was a questionnaire of a qualitative and quantitative research, with questions that dealt with gender distribution in the labor market, age, education, whether it is registered or not, performance of enterprises, among other characteristics. Among some facts, it was found that in the city of Doctor Severiano the predominant sex is male and as for education most entrepreneurs have completed high school. All these factors point to the economic development of the researched city.
Monografia
Keywords: Empreendedorismo; Doutor Severiano – RN; Desenvolvimento econômico; Entrepreneurship; Doctor Severiano - RN; Economic development; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA